Estimating body size in the large carpenter bees (Xylocopa) - Ostwald, Madeleine; Hirokawa, Ryan; Smith, Colleen; Rivas Trasvina, Sheccid; Seltmann, Katja (Journal of Melittology, 2025)
Body size is a salient functional trait in bees, with implications for reproductive fitness, pollination ecology, and responses to environmental change. Methods for quantifying bee body size commonly rely on indirect estimates and vary widely across studies, particularly in studies of the large carpenter bees (Xylocopa Latreille) (Apidae: Xylocopinini). We evaluate the robustness of three common body size parameters (intertegular distance, head width, and costal vein length) as predictors of dry body mass within and among 11 species of Xylocopa (and 5 subspecies). We found that all three size measurements provide robust body size estimates, accounting for 92–93% of intraspecific variation in body mass. Within species, however, these measurements were considerably less predictive of body mass, explaining on average only 36.8% (intertegular distance), 57.4% (head width), and 38.8% (costal vein length) of the variation in body mass. We also highlight a novel application of photogrammetry and 3D modeling to estimate surface area and volume across species, and comment on the utility of these methods for body size estimates in Xylocopa and in insects more broadly. These findings provide practical guidelines for body size estimation methods within and among carpenter bee species.